Improvement in lipids after switch to boosted atazanavir or darunavir in children/adolescents with perinatally acquired HIV on older protease inhibitors: results from the Pediatric HIV/AIDS Cohort Study. Issue 3 (21st November 2017) - Jao, J; Yu, W; Patel, K; Miller, TL; Karalius, B; Geffner, ME; DiMeglio, LA; Mirza, A; Chen, JS; Silio, M; McFarland, EJ; Van Dyke, RB; et al.
Abstract : Objectives: Dyslipidaemia is common in perinatally HIV‐infected (PHIV) youth receiving protease inhibitors (PIs). Few studies have evaluated longitudinal lipid changes in PHIV youth after switch to newer PIs. Methods: We compared longitudinal changes in fasting lipids [total cholesterol (TC), triglycerides (TG), low‐density lipoprotein cholesterol (LDL‐C), high‐density lipoprotein cholesterol (HDL‐C), and TC:HDL‐C ratio] in PHIV youth enrolled in the Pediatric HIV/AIDS Cohort Study (PHACS) Adolescent Master Protocol (AMP) study who switched to atazanavir/ritonavir (ATV/r)‐ or darunavir/ritonavir (DRV/r)‐based antiretroviral therapy (ART) from an older PI‐based ART and those remaining on an older PI. Generalized estimating equation models were fitted to assess the association of a switch to ATV/r‐ or DRV/r‐based ART with the rate of change in lipids, adjusted for potential confounders. Results: From 2007 to 2014, 47 PHIV children/adolescents switched to ATV/r or DRV/r, while 120 remained on an older PI [primarily lopinavir/r (72%) and nelfinavir (24%)]. Baseline age ranged from 7 to 21 years. After adjustment for age, Tanner stage, race/ethnicity, and HIV RNA level, a switch to ATV/r or DRV/r was associated with a more rapid annual rate of decline in the ratio of TC:HDL‐C. ( β = −0.12; P = 0.039) than remaining on an older PI. On average, TC declined by 4.57 mg/dL/year ( P = 0.057) more in the switch group. A switch to ATV/r or DRV/r was not associated with the rate of HDL‐C, LDL‐C, or TG change. Conclusions: A switch to ATV/r or DRV/r may result in more rapid reduction in TC and the TC:HDL‐C ratio in PHIV youth, potentially impacting long‐term cardiovascular disease risk.